Comprehensive reporting of pelvic floor muscle training for urinary incontinence: CERT-PFMT. (September 2021) - Slade, Susan C.; Morris, Meg E.; Frawley, Helena; Hay-Smith, Jean
Abstract: Aim: To produce a pelvic floor muscle training variation of the Consensus on Exercise Reporting Template (CERT-PFMT). Methods: Qualitative methods were used to explore the perspectives of physiotherapists who have postgraduate continence and pelvic floor rehabilitation qualifications on using research evidence to implement pelvic floor muscle training for urinary incontinence. The same experienced facilitator guided the discussions with questions derived from systematic reviews and content experts. The face-to-face focus groups were audio-recorded and verbatim transcripts were thematically analysed. For each CERT item the authors collated participant quotations that identified required explanation or elaboration for the CERT-PFMT. Systematic reviews of pelvic floor muscle training for urinary incontinence were searched by the research team for examples of good reporting. Results: Twenty- nine continence physiotherapists participated in one of seven focus groups. Participants agreed that all key elements they needed for replicating pelvic floor muscle training interventions from a research report were provided in the published CERT checklist. CERT items 2 (qualifications), 6 (motivation), 7 (progression rules), 8 (exercise description), 13 (intervention description) and 15 (starting level) required additional explanations for pelvic floor muscle training. Clinicians reported that original CERT explanations for items 1, 3–5, 8–12, 14 and 16 could be used without modification. Conclusions: The CERT-PFMT reporting guideline has been designed with clinician input to inform how to document pelvic floor muscle training to enable replication in clinical practice. It can be used for research protocols, to construct manuscripts reporting pelvic floor muscle training for urinary incontinence and by journal editors and reviewers.